A Mechanistic Framework for Explaining Audience Design in Language Production. [article]. - Ferreira, Victor S.
Audience design refers to the situation in which speakers fashion their utterances so as to cater to the needs of their addressees. In this article, a range of audience design effects are reviewed, organized by a novel cognitive framework for understanding audience design effects. Within this framework, feedforward (or one-shot) production is responsible for feedforward audience design effects, or effects based on already known properties of the addressee (e.g., child versus adult status) or the message (e.g., that it includes meanings that might be confusable). Then, a forward modeling approach is described, whereby speakers independently generate communicatively relevant features to predict potential communicative effects. This can explain recurrent processing audience design effects, or effects based on features of the produced utterance itself or on idiosyncratic features of the addressee or communicative situation. Predictions from the framework are delineated." -- (from the author)
Keywords: Audience design; Language production; Forward modeling; Predictions